The sense of justice and criminal law: Coming to terms with enforced disappearances in Turke - Ünaldı, Cemre. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2018., 2018)
During 1980s and 1990s, enforced disappearances, which is generally known in Turkey as being “missing in custody,” became prevalent in the regime’s hands as a means of suppressing the regime’s opponents. It has been important in Southeast Anatolia which became state of emergency. It is admitted that enforced disappearances were executed with the agency of paramilitary forces that are not formally part of the state but were condoned by government. Beginning in the 2000s, especially after the declaration of Turkey’s candidacy for full-membership in the EU, coping with past abuses such as enforced disappearances became prominent, and transitional justice mechanisms have been used. But the absence of political will to disclose the truth and the insuﬃciency of Turkey’s judicial system have led to obstacles in this process. In the peace process, it has been believed that peace can be constructed without justice for past atrocities. However, I argue that to demand peace and create reconciliation in a society that has experienced human rights violations, the sense of justice of this society should be satisfied. Retributive justice means are an adequate, indispensable way to do justice. I inquire into the role of retributive justice mechanisms in generating a sense of justice visa-vis past human rights abuses and more specifically in cases of enforced disappearances in Turkey by examining Turkish legal system, the conduct of the judiciary, the perspective of cause lawyers who work on this crime, international criminal law, and case studies of states that experienced enforced disappearances.
Keywords: Disappeared persons -- Turkey.; Turkey -- Politics and government -- 1980-; Political violence -- Turkey.